Childcare and Mothers' Labor Market Outcomes in Lower- and Middle-Income Countries. (12th July 2022) - Halim, Daniel; Perova, Elizaveta; Reynolds, Sarah
Abstract: Improving women's labor force participation and the quality of their employment can boost economic growth and support poverty and inequality reduction; thus, it is highly pertinent for the development agenda. However, existing systematic reviews on female labor market outcomes and childcare, which can arguably improve these outcomes, are focused on developed countries. We review 22 studies which plausibly identify the causal impact of institutional childcare on maternal labor market outcomes in lower-and-middle income countries. All but one study finds positive impacts on the extensive or intensive margin of maternal labor market outcomes, which aligns with findings from developed countries. We further analyze aspects of childcare design, including hours, ages of children, coordination with other childcare services that may increase the impacts on maternal labor market outcomes. We conclude with a discussion of directions for future research.